An assessment of democratic vulnerability: regime type, economic development, and coups d'état. Issue 8 (17th November 2019) - Schiel, Rebecca E.
ABSTRACT: Prior research has not established a clear relationship between democracy and insulation from coups d'état, with very few studies illustrating robust findings on the subject. I contend that the lack of attention paid to the conditional influences of democracy on coups has resulted in these mixed findings. I posit that insulation from coups occurs at higher levels of economic development in both autocracies and democracies. However, the vulnerability present at low levels of economic development is significantly greater in democracies. Poor democracies lack the coercive capacity associated with authoritarian states, suffer from relatively weaker patronage networks, and have smaller pots for public goods provision, all making them less capable of maintaining elite loyalty. An assessment of 165 states for the years 1950–2011 offers strong support for the argument. Democracies are indeed an important part of the coup story, but only when simultaneously addressing their level of economic development.